Optical wireless communication and internet of things - Zaichen ZHANG; Xiaohu YOU; Jian DANG; Liang WU; Bingcheng ZHU; Ji CHEN; Lei WANG (物联网学报)
Optical wireless communication (OWC) entitles many advantageous properties such as unlicensed spectrum, high electromagnetic compatibility, compared with its radio frequency wireless counterpart, which enables it to be a potential important driving factor for the diverse developments of future internet of things (IoT).Starting from the optical sources and optical devices, some basic principles and limitations of OWC were introduced.Then, some key technologies, including channel modeling, signal modulation, array communication and high-precision positioning were discussed.Based on those and according to the requirements on peak data rate, sensing precision, energy transfer and security and confidentiality of the next generation IoT, the role of OWC as a technological enabler for next generation IoT was analyzed.Finally, related conclusions were given.